Factors Related to Water Filter Use for Drinking Tap Water at Home and Its Association with Consuming Plain Water and Sugar-Sweetened Beverages Among US Adults. (29th May 2020) - Park, Sohyun; Onufrak, Stephen; Cradock, Angie; Hecht, Christina; Patel, Anisha; Chevinsky, Jennifer; Blanck, Heidi
Abstract: Objectives: Drinking plain water, especially as a substitute for sugar-sweetened beverages (SSB), may improve diet and prevent chronic disease. There is limited information on how water filter use impacts intake of beverages. We explored factors associated with water filter use for drinking tap water at home and examined its association with consuming plain water and SSB. Methods: We used the 2018 SummerStyles data for 4042 US adults (≥18 y). For a first model, outcome was water filter use (yes vs. no or do not drink tap water at home). For a second model, outcomes were intake of plain water (tap and bottled water) and SSB (regular soda, fruit drinks, sports/energy drinks, sweetened coffee/tea drinks), and exposure was water filter use. Covariates included sociodemographics, weight status, Census regions, and ownership status of living quarters. Four multivariable logistic regressions were used to estimate adjusted odds ratios (AOR) for consuming tap water, bottled water, or total plain water >3 cups/d (vs. ≤3 cups) and SSB ≥ 1 time/d (vs. <1 time) by water filter use. Results: Overall, 36% of adults reported using a filter for drinking tap water at home and 14% did not drink tap water at home. Factors significantly associated with lower odds of using a water filter were being non-Hispanic (NH) black (AOR = 0.72, vs. NH white), lower education (AOR = 0.61 for ≤ high school; AOR = 0.69 for some college, vs. college graduate), not married (AOR = 0.78 vs. married/domestic partnership) and lower household income (AOR = 0.70 for <$35, 000 vs. ≥$100, 000). After adjusting for covariates, using a water filter was significantly associated with higher odds for drinking >3 cups/d of tap water (AOR = 1.33) and lower odds for consuming SSB ≥ 1 time/d (AOR = 0.76). Not drinking tap water at home was significantly associated with lower odds for drinking >3 cups/d of tap water (AOR = 0.39) and higher odds of drinking >3 cups/d bottled water (AOR = 3.46). Conclusions: Using a filter for drinking home tap water was associated with higher tap water intake and lower SSB intake among US adults. Yet, water filter use was lower among Black adults and those with lower income and education compared to other groups. While filters can improve tap water quality and healthful beverage habits, some may reduce fluoride content and their cost and proper use should be considered. Funding Sources: Solely for author's time from their institutions.